(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
An experiment of algal culture was conducted in natural light and temperature conditions at a balcony of a room at the 2nd floor of Fisheries Faculty Building facing the north. The experiment was done to evaluate the growth of Chlorella ellipsoidea in four different media, viz, medium I (inorganic), medium II (organic, whole pulse powder extract), medium III (organic, whole lentil powder extract) and medium IV (organic, whole gram powder extract) under natural environment conditions during January-June, 2015. Growth rates of the algal species in four different media were found not significantly different. The alga, C. ellipsoidea attained maximum cell density of 28.89×106 cell ml-1 in the 15th day in medium I, of 30.69×106 cell ml-1 in the 13th day in medium II, of 26.18×106 cell ml-1 in the 15th day in medium III and of 21.12×106 cell ml-1 in the 13th day in medium IV. The ranges of air temperature, water temperature and light intensity were 21°C to 38°C, 23°C to 36°C and 2.28×103to 9.60×103 Lux respectively during the culture period. The average sunshine period was 5.87±2.82 hrs. Total alkalinity, free CO2, pH , NO3-N and PO4-P of algal culture media I, II, III and IV were 128, 540, 554 and 322 mgL-1; 32, 162, 102, 70 mgL-1; 7.4, 8, 7.9 and 7.9; 180, 36.6, 62.4 and 150 mgL-1, and 25.2, 48.2, 42.4 and 45.6 mgL-1, respectively. According to ANOVA of cell densities of cultures of C. ellipsoidea under treatments are not significantly different (F=1.441077). It is clear that differences between them are not significant i.e. mean algal cell densities are more or less same as differences between treatments are less than 20%. Int. J. Agril. Res. Innov. & Tech. 7 (1): 51-57, June, 2017